BRAF inhibitor monotherapy in BRAFV600E-mutated pediatric low-grade glioma: a single center’s experience - McThenia, S. S.; Reddy, K. M.; Damaraju, E.; Castellino, E.; He, Z.; Beer, R.; Chien, F.; Castellino, R. C.; Goldman-Yassen, A. E.; Fangusaro, J. R.; MacDonald, T. (Frontiers in Oncology, 2025)
BackgroundPediatric low-grade gliomas (pLGGs) have an overall survival of over 90%; however, patients harboring a BRAFV600E alteration may have worse outcomes, particularly when treated with classic chemotherapy. Combined BRAF/MEK inhibition following incomplete resection demonstrated improved outcome in BRAFV600E altered pLGG compared to combined carboplatin/vincristine chemotherapy and is now considered the standard FDA-approved treatment for this group of tumors. The aim herein was to investigate the efficacy and tolerability of single agent BRAF inhibitor treatment in BRAFV600E altered pLGG.MethodsA single institution retrospective chart review analysis was performed on patients, 0 to 21 years of age, with newly diagnosed and/or progressive BRAFV600E mutated pLGGs (WHO Grade 1 or 2) at Children’s Healthcare of Atlanta treated off-study with BRAF inhibitor monotherapy between 2013-2023. 2-year progression free survival (PFS) and objective tumor response was evaluated. All toxicities possibly associated with BRAF inhibition therapy were evaluated and described according to Common Terminology Criteria for Adverse Events version 5 (CTCAEv5). MRI brain imaging data at baseline and best response was evaluated to identify patterns that may predict response to BRAF inhibition monotherapy.ResultsFifteen patients diagnosed with BRAFV600E mutated pLGG, treated with monotherapy BRAF inhibition, were identified. Median age of diagnosis: 3.8 years (0.2 –18.1). Histologic diagnosis: pilocytic astrocytoma (PA) (N=4); ganglioglioma (GGL) (N=3); GGL, atypical (N=3); pleomorphic xanthroastrocytoma (PXA) (N=2); low-grade neuroepithelial tumor (N=1); infiltrating glioma (N=1); and LGG (NOS) (N=1). Tumor locations included: hypothalamus/optic chiasm (N=6); brainstem (N=4); third ventricle/thalamus (N=2); parietal/temporal lobe (N=2); and spinal cord (N=1). Mean duration of BRAF inhibitor monotherapy: 38.41 months (range 3.9-83.7). Median follow-up: 32.6 months (16 - 78.1). Two-year PFS for patients on BRAFi monotherapy for at least 10 months: 90% (95% CI: 73.2%-100%). Objective Response (OR) for 15 evaluable patients on BRAF inhibitor (BRAFi) therapy: 73% (0/15 CR + 6/15 PR + 5/15 MR) with Overall Response Rate (ORR=CR+PR): 40%. Overall, patients tolerated treatment well with Grade 1 rash being the most common toxicity. Two of 15 patients (13%) discontinued therapy due to toxicities, and 2 other patients switched within drug class from vemurafenib to dabrafenib due to toxicities.DiscussionIn this small cohort of incompletely resected BRAFV600E mutated pLGGs, BRAFi monotherapy was effective and well tolerated with an ORR comparable to published prospective outcomes of dual MEK/BRAF inhibitor therapy. This promising monotherapy treatment should be considered when choosing treatment for incompletely resected BRAFV600E-altered pLGGs.